<griech.> Persikòn dé kárta ho strátos dôron: A Typical Persian Gift (Hdt. IX 109) - Sancisi-Weerdenburg, Heleen
auch zu PT 6 und Stolper, Entrepreneurs p. 62 and p. 25: "estate of the Lady of the Palace".